Analysis of Factors Affecting Leadership at Bank DKI Jakarta Selatan Post Covid-1 - Herawaty Purnama, Yanthy; Desty Febrian, Wenny; Hikmah Perkasa, Didin; Al Faruq Abdullah, Muhamad; Apriani, Ari; ., Windayanti (KnE Social Sciences, 2023)
This study aims to see the factors influencing leadership at Bank DKI South Jakarta. The variables in this study are organizational culture, motivation, work environment, and leadership after the Covid-19 pandemic. A survery research with a quantitative descriptive approach was conducted on all employees of bank DKI Jakarta, and 58 samples were taken from all employees of Bank DKI South Jakarta. Quantitative data tools, namely SEM PLS was used for data processing. Data collection methods: The data collection techniques carried out are interviews, questionnaires, observations, interviews. Research results: Based on the table obtained R-Square values for constructs X1, X2, and X3 of 0.707, which means that these values can identify Y and can be explained by variables X1, X2, and X3 by 70.7% while the rest is influenced by other variables outside the study. Keywords: leadership, organizational culture, motivation, work environment